CARDIOVASCULAR EFFECTS OF SELECTIVE COX-2 INHIBITORS IN RHEUMATIC DISEASES - Rimma Mikhailovna Balabanova (Современная ревматология, 2010)
The paper gives data on the effects of nonsteroidal anti-inflammatory drugs on the cardiovascular system in patients with rheumatoid arthritis and osteoarthrosis. The use of selective COX-2 inhibitors (Naiz) versus diclofenac is not shown to elevate blood pressure